Positive Youth Development, Life Satisfaction, and Problem Behaviors of Adolescents in Intact and Non-Intact Families in Hong Kong - Shek, Daniel T. (Frontiers in Pediatrics, 2013)
This study investigated whether Chinese adolescents living in intact and non-intact families differed in their positive development, life satisfaction, and risk behavior. A total of 3,328 Secondary 1 students responded to measures of positive youth development (such as resilience and psychosocial competencies), life satisfaction, and risk behavior (substance abuse, delinquency, Internet addiction, consumption of pornographic materials, self-harm, and behavioral intention to engage in problem behavior). Findings revealed that adolescents growing up in intact families reported higher levels of positive developmental outcomes and life satisfaction as compared with adolescents from non-intact families. Adolescents in non-intact families also reported higher levels of risk behaviors than those growing up in intact families.